(untitled) (Asian Journal of Pharmaceutics (AJP), 2021)
Introduction: Surgical site infections (SSIs) are the most prevalent healthcare-associated infections that increase mortality and morbidity rates. Aim: The present study was a retrospective study that aimed to determine the post-operative SSI rate in a public hospital in Al-Kharj. Materials and Methods: The data were collected by the microbiology laboratory in the hospital and included the number of infections caused by Gram-positive and Gram-negative bacteria and the number of SSIs in the hospital. Results: Most of the infections in the present study were caused by Gram-negative organisms (83.00%). The most common bacteria were Pseudomonas aeruginosa (19.87%) followed by Escherichia coli (16.34%) and Klebsiella pneumoniae (13.13%). The SSI rate in the hospital was 2.32% (=21/906*100%). Most of the SSIs were caused by Gram-negative bacteria (80.95%). Most of the SSIs were caused by Staphylococcus aureus (19.04%), P. aeruginosa (14.29%), Proteus mirabilis (14.29%), Acinetobacter (14.29%), and Citrobacter (14.29%). Conclusion: The SSIs rate in Al-Kharj city is low but adopting protocols for surveillance and implementing guidelines are still needed to minimize the SSIs rate.